The Effect of Fishbowl Technique on Pupils' Literary Awareness - Abdurrahman, Israa Burhanuddin; Ahmed Jasim, Ghaidaa Ahmed Jasim; Mohammed Badie, Muthana (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2024)
The purpose of this study is to examine the effect of Fishbowl Technique on EFL Iraqi preparatory pupils’ literary awareness. This study hypothesizes that there is no significant difference in the level of literary awareness between the experimental and control groups. The study uses a Non-Randomized Experimental Group Design and includes a sample of 60 students from the fifth scientific stage at Al-Hikma School for Girls in Al-Alam town in Saladdin, Iraq. Thirty students are in the experimental group Section A and thirty students are in the control group Section B. The study took place over a two-month period, with the researcher instructing two groups of pupils during the academic year 2024-2023. Various statistical methods, including weighted mean and percentile mean, were utilized to assess the pupils' awareness. The analysis of the data showed that teaching pupils using the Fishbowl technique was effective in improving their literary awareness. The findings led to conclusions, recommendations, and suggestions for future research.